Dissolved organic phosphorus utilization by the marine bacterium Ruegeria pomeroyi DSS‐3 reveals chain length‐dependent polyphosphate degradation. (1st February 2022) - Adams, Jamee C.; Steffen, Rachel; Chou, Chau‐Wen; Duhamel, Solange; Diaz, Julia M.
Summary: Dissolved organic phosphorus (DOP) is a critical nutritional resource for marine microbial communities. However, the relative bioavailability of different types of DOP, such as phosphomonoesters (P‐O‐C) and phosphoanhydrides (P‐O‐P), is poorly understood. Here we assess the utilization of these P sources by a representative bacterial copiotroph, Ruegeria pomeroyi DSS‐3. All DOP sources supported equivalent growth by R . pomeroyi, and all DOP hydrolysis rates were upregulated under phosphorus depletion (−P). A long‐chain polyphosphate (45polyP) showed the lowest hydrolysis rate of all DOP substrates tested, including tripolyphosphate (3polyP). Yet the upregulation of 45polyP hydrolysis under −P was greater than any other substrate analyzed. Proteomics revealed three common P acquisition enzymes potentially involved in polyphosphate utilization, including two alkaline phosphatases, PhoD and PhoX, and one 5′‐nucleotidase (5′‐NT). Results from DOP substrate competition experiments show that these enzymes likely have broad substrate specificities, including chain length‐dependent reactivity toward polyphosphate. These results confirm that DOP, including polyP, are bioavailable nutritional P sources for R . pomeroyi, and possibly other marine heterotrophic bacteria. Furthermore, the chain‐length dependent mechanisms, rates and regulation of polyP hydrolysis suggest that these processes may influence the composition of DOP and the overall recycling of nutrients within marine dissolved organic matter.